1996
DOI: 10.1093/oxfordjournals.eurheartj.a014903
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in relation to educational level in 36 000 men and women in the Netherlands

Abstract: The study objective was to describe the associations between socioeconomic status and (concurrence of) cardiovascular risk factors. The Netherlands Monitoring Project on Cardiovascular Risk Factors is a screening project that was carried out from 1987-1991 in three cities. Cross-sectional data were obtained on educational level and on the prevalence of smoking, alcohol intake, physical inactivity, obesity, hypertension, hypercholesterolaemia and low HDL-cholesterol. A total of 36 000 men and women, aged 20-59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 32 publications
6
58
2
1
Order By: Relevance
“…9 This was also the case in another survey, in a younger population in the same country. 16 The findings related to women are in keeping with previous reports in other countries: more women than men were in the lower occupational categories and health differences were more pronounced when educational level rather than occupational category is taken into an account. 17,18 Similarly, job strain has been observed to be a risk factor for high blood pressure in men, but not in women.…”
Section: Discussionsupporting
confidence: 89%
“…9 This was also the case in another survey, in a younger population in the same country. 16 The findings related to women are in keeping with previous reports in other countries: more women than men were in the lower occupational categories and health differences were more pronounced when educational level rather than occupational category is taken into an account. 17,18 Similarly, job strain has been observed to be a risk factor for high blood pressure in men, but not in women.…”
Section: Discussionsupporting
confidence: 89%
“…In one study an inverse association was found and in two, no association was found Europe-outside UK: Inverse associations of SES with BP and hypertension have been reported in (Table 3). In the Kenyan Luo Migration study there was a positive correlation between years of edusome parts of Sweden 35-37 but not others, 38 in Norway, 39 Paris, 40 the Netherlands 41,42 and in Ireland. 43 cation and systolic and diastolic BP adjusted for age, 58 and in a Nigerian occupational cohort a direct In Finland the association among men was not present in 1972 but has emerged recently 4,44 and an association with hypertension prevalence was also found.…”
Section: Grade Occupation Ethnic Group Psycho-social Andmentioning
confidence: 92%
“…13 In the Health Survey for England with other variables. 19,28,30,34,39,42,46,49,51,57 The specific effect of alcohol adjustment was reported separ-(1994), obesity is considerably more prevalent in women of lower social class, although this is not ately in just one of these studies. Adjusting for alcohol alone approximately halved the SES gradient in true of males.…”
Section: Grade Occupation Ethnic Group Psycho-social Andmentioning
confidence: 95%
See 1 more Smart Citation
“…A large number of studies have documented a powerful association between CVD and socio-economic status (SES), whether measured by education, income or occupation [11][12][13][14][15][16][17][18]. However, only a few studies have reported on the relative importance of both biomedical and psycho-social factors as predictors of acute myocardial infarction (AMI) in the population.…”
Section: Introductionmentioning
confidence: 99%